2012
DOI: 10.1007/s13197-012-0836-3
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antiproliferative activities of phenolics isolated from fruits of Himalayan yellow raspberry (Rubus ellipticus)

Abstract: Yellow Himalayan raspberry, a wild edible fruit, was analyzed for phenolic contents, and antioxidant, antibacterial and antiproliferative activities. Phenolics were extracted using 80 % aqueous solvents containing methanol, acidic methanol, acetone and acidic acetone. Our analysis revealed that the acidic acetone extracts recovered the highest level of total phenolics (899 mg GAE/100 g FW) and flavonoids (433.5 mg CE/100 g FW). Free radical scavenging activities (DPPH, ABTS, superoxide and linoleate hydroperox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 36 publications
2
28
0
Order By: Relevance
“…As polyphenols and anthocyanins are well-documented antioxidants exhibiting antibacterial action [64,65,66,67,68], it is reasonable to hypothesize that the capacity to inhibit bacterial growth of the investigated wines may be related to the concentration of these compounds.…”
Section: Resultsmentioning
confidence: 99%
“…As polyphenols and anthocyanins are well-documented antioxidants exhibiting antibacterial action [64,65,66,67,68], it is reasonable to hypothesize that the capacity to inhibit bacterial growth of the investigated wines may be related to the concentration of these compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The level of total phenolics and flavonoid content observed in this study was higher than the previously reported values of the species in Garhwal region of Uttarakhand Himalaya (5.50 mg GAE/g fw and 1.79 mg CE/g fw in methanolic extract) (Saini et al . ) and from Western Ghats (0.72 mg GAE/g fw and 0.864 mg QE/g fw) (Karuppusamy et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…Antioxidant, antibacterial and anti‐proliferative activities of R. ellipticus have already been investigated (Saini et al . ). However, little information is available on antioxidant activity, phenolics and other chemical constituents (Karuppusamy et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…DPPH is a stable diamagnetic free radical, dissolved in organic solvents such as methanol and ethanol. Dissolved DPPH radical in solvents visible as intense All values denoted in triplicates Mean ± SD The optical density values are represented with Mean ± SD measurements All Values are triplicates and calculated with Mean ± SD violet colour (oxidised state) and they would be stable by accepting hydrogen or electron followed by proton from donor gives a colourless product (reduced state) (Saini et al 2014). The increase intensity of colourless product decreases the absorbance, whereas, the decrease in colourless intensity increases the absorbance at wavelength 517 nm.…”
Section: Gc-ms and Hr-lc/q-tof/ms Analysis For Phytochemical Profile mentioning
confidence: 99%